Polyhydroxyalkanoates as biomaterials - Bhagyashri, S.; Gadgil, Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2017)
Polyhydroxyalkanoates (PHAs) are biopolymers synthesized by bacteria under unbalanced growth conditions. These biopolymers are considered as potential biomaterials for future applications because they are biocompatible, biodegradable, and easy to produce and functionalize with strong mechanical strength. Currently, PHAs are being extensively innovated for biomedical applications due to their prerequisite properties. The wide range of biomedical applications includes drug delivery systems, implants, tissue engineering, scaffolds, artificial organ constructs, etc. In this article we review the utility of PHAs in various forms (bulk/nano) for biomedical applications so as to bring about the future vision for PHAs as biomaterials for the advancement of research and technology.
Keywords: Biomedical Applications; Cancer-therapy; Drug-delivery Systems; In-vitro; Molecular-weight; Poly(Ester Urethane)S; poly(ethylene glycol); Regenerative Medicine; Tissue Engineering Applications; Vitro Antibiotic Release

Polyhydroxyalkanoates as biomaterials (vol 8, pg 1774, 2017) - Gadgil, Bhagyashri S. Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2019)
Correction for `Polyhydroxyalkanoates as biomaterials' by Bhagyashri S. Thorat Gadgil et al., Med. Chem. Commun., 2017, 8, 1774-1787.